EXISTENCE OF INVARIANT POINTS AND APPLICATIONS TO SIMULTANEOUS APPROXIMATION - Chandok, Sumit; Narang, T. D. (Bulletin of Natural Sciences Research, 2022)
For the set of ε-simultaneous approximation and ε-simultaneous coapproximation, we derive certain BrosowskiMeinardus type invariant point results in this paper. As a consequence, some results on ε-approximation, εcoapproximation, best approximation, and best coapproximation are also deduced.